Pengaruh Ekstrak Tembuluk Kelapa Merah (Cocos nucifera var. rubesces) Terhadap Penurunan Kadar Kolesterol Pada Mencit (Mus musculus) - Zasmita, Eka; Sutrisnawati, Sutrisnawati; Ramadhan, Achmad; Trianto, Manap; Masrianih, Masrianih; Kundera, I Nengah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of red coconut tembuluk extract (Cocos nucifera var. rubescens) on lowering blood cholesterol levels in mice (Mus musculus). The research method used is the true experimental method (Experimental Research) using a completely randomized design (CRD). The number of samples used was 24 mice consisting of 6 groups and 5 replications. The normal control group (KO) was only fed and watered ad libitum, the positive control group (K+), negative control (K-) and the PI, PII, PIII treatment groups were induced with LDL for 17 days. The positive control group (K+) was given simvastatin 0.026 mg/20 BW. The normal control group (KO) and the negative control group (K-) were fed and watered ad libitum, the PI, PII, PIll treatments were induced with red coconut tembuluk extract with different concentrations. Treatment group I (PI) was induced with a concentration of 40% red coconut tembuluk extract, treatment group II (PII) was induced with a concentration of 60% red coconut tembuluk extract, and treatment group III (PIII) was induced with a concentration of 80% red coconut tembuluk extract. The observation data were analyzed using the One-Way ANOVA test. The results of the study showed that the administration of red coconut turmeric extract had an effect on reducing blood cholesterol levels in mice induced by LDL (pork fat). The red coconut turmeric extract that was effective in reducing blood cholesterol levels was a concentration of 40% (PI) where the average result of blood cholesterol level measurements was 118.4 mg/dl.